MYTH OR REALITY? MUSLIM‟S IMAGE AT THE CROSSROAD - Mohamed Abdel-Hady, Zakaryya (European Scientific Journal, ESJ, 2014)
Despite the fact that Islam is a cosmopolitan religion with over 1.5billion followers with extreme ethnic diversity and a wide range of culturesand languages, Western media presents a stereotype in which Muslims are astatic, barbaric, and uncivilized people. Islam is often perceived in mediareports as a major obstacle to the advancement of globalization, withfollowers holding beliefs incompatible with the modern life. Muslimsconstantly find themselves in a defensive struggle, having to answer to theperceptions, misconceptions and even prejudices of others. They arefrequently questioned about their morality, history and even their intentions.These perceptions, which verge on paranoia and Islamophobia, areaccompanied by persistent ignorance of Islam, its teaching and its diversity.Since the collapse of the Soviet Union, Western strategists have continuouslydiscussed the question of who will be the next challenge to the West. Withthe events of 9/11 and later, the question of the loyalty of Muslims inWestern societies and the possibility of peaceful coexistence has come underheavy scrutiny. Today, recognizing the extent of globalization and the rolethat media plays in influencing and manipulating world opinion, it becomescrucial to re-examine, and maybe to re-construct, the Muslim image.This paper attempts to explore the formulation of the current image of Islamand Muslims in the West and the role media plays in shaping the globalimage of Muslim. In doing so, the following specific factors will bediscussed:(1) the influence of the media in creating Islamophobia, (2) the acuteignorance in the West of Islam and Muslim cultures; and finally, (3)Muslims own contribution in sketching such image.